Pengaruh Intellectual Capital Terhadap Nilai Perusahaan Perbankan Indonesia (Studi empiris pada perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia tahun 2013-2016) - Riaty Handayani (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2020)
Research that examines the effect of intellectual capital on firm’s market value shows different results. The firm’s market value can be reflected in the price investors pay for their shares in the market. The purpose of this study to determine the effect of Intelectual Capital component consisting of Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), Capital Employed Efficiency (CEE) to firm’s market value (PBV). The population in this study is banking companies listed on the Indonesia Stock Exchange in 2013-2016. The sample of this research is 100 from 25 banking companies. Sampling technique through purposive sampling method. Researchers used the VAIC ™ method by Pulic, using multiple linear regression analysis. The partial hypothesis test showed that there only Capital Employed Efficiency (CEE) has positive and significant influenceto firm’s market value, while Human Capital Efficiency (HCE) and Structural Capital Efficiency (SCE) have no effect on firm’s market value. While based on hypothesis test result simultaneously showed that Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), Capital Employed Efficiency (CEE) together have significant influence to firm’s market value.